Chrysippus’ Conditional Captured from a Non-Axiomatic Computer Program - Miguel López-Astorga (Organon F)
It is usually accepted that Chrysippus of Soli proposed the “connexivist view” of the conditional. I assume here that Chrysippus also supported the “inclusion view” and that differentiated between two kinds of conditionals: strong and weak conditionals. The latter assumptions allow me to link Chrysippus’ interpretation of the conditional to a computer program such as Non-Axiomatic Reasoning System (NARS). The inclusion view enables to deem Stoic conditionals as inheritance relations in NARS. The distinction between strong and weak conditionals helps assign values of frequency and confidence such as those NARS inheritance relations have to Stoic conditionals.